A Retrospective Observational Study of Adverse Reactions Associated With Intravenous Immunoglobulin Infusion - Kato, Hidefumi; Hayashi, Megumi; Ohashi, Wataru; Yamaguchi, Takamasa; Tanaka, Satomi; Kozono, Ayumi; Gao, Siqiang; Katai, Akiko; Niwa, Reiko; Matsuo, Tomohito; Ishiyama, Kazuki; Ando, Takanori; et al. (Frontiers in Immunology, 2021)
Background Although intravenous immunoglobulin (IVIG) therapy is generally safe and well tolerated, adverse reactions (ARs) do occur. The majority of these ARs are mild and transient. Risk factors for ARs associate with IVIG infusions are not well established. This study investigated possible risk factors influencing the occurrence of IVIG-associated ARs. Study Design and Methods This was a retrospective observational analysis of data accumulated over 5 years, including patient demographics, clinical condition, IVIG dosing regimens, number of IVIG infusions, and any ARs. Results ARs were associated with IVIG in 4.9% of patients and 2.5% of infusions. By univariate analyses, ARs correlated with female sex, adult age, high dose IVIG, and autoimmune disease. Multivariate logistic regression identified three statistically significant of risk factors: on a per-patient basis, being female (p=0.0018), having neuromuscular disease (p=0.0002), and receiving higher doses of IVIG per patient body weight (p<0.001), on a per-infusion basis, being female (p < 0.001), being adolescents to middle age (p < 0.001), and having neuromuscular disease (p < 0.001). Conclusion Neuromuscular disease emerged as one of the significant factors for ARs to IVIG.